Informe sobre reptiles colombianos. iii: investigaciones sobre la anatomía craneal; distribución geográfica y ecología de crocodylus intermedius (graves) en colombia (1958)
1. The present paper includes studies about the Cranial Anatomy, Geographical Distribution and Ecology of Crocodylus intermedius in Colombia.    2. The material has been collected from the areas of the rivers Guaviare, Ariari, Güéjar and Cunimía. It consists of sixteen skulls and fifty-four fetus-containing eggs.                                                          3. A detailed description of the skulls is given, the lengths of which range between 25.4 cm. and 70.7 cm.                                                                                 4. Concerning the scalation: there is a single row of occipitals containing between 2 and 6 individual scutes: two rows of cervicals, the first containing 4 and the second 2 scales. The dorsals are in 16-17 transverse rows, the broadest of which contains 5-6 individual scales. The ventrals are in 25 to 27½ transverse, rows, the broadest of which contains between 14 and 18 individual scales. The tail has between 17 and 19 double-crested, and 17 to 19 single-crested segments.  The scalation of 4 fetus does not show any special characteristics.              5. The coloration of Cr. intermedius varies between light-grey in juveniles and greyish green, light brown to yellowish in adults. The greenish color is due to the extensive growth of algae on the dorsal side. There are dark marks and spots on the entire dorsal and lateral sides as well as on the ventral side of the tail. The throat and belly are white and without marks. The colour of living specimens on sand banks, in bright sun appears almost white.               6. Cr. intermedius ranges, in Colombia, between the Rio Arauca in the east and the lower course of the Río Duda in the west. No intermedius are to be found in the rivers Vaupés. Caquetá and Putumayo (tributaries of the Amazon). In Venezuela he ranges as far as San Fernando de Atabapo in the upper Orinoco area. For unexplainable reasons he does not enter the Amazon, by the comunicatron of the Orinoco-Casiquiare-Río Negro.                                  7. Numerous ecological observations were made on habitat, size, alimentation, parasites, reproduction and behavior. The "record" in size is apparently shown by an old male, which, according to Humboldt was 22 feet 3 inches long (6.78 meters). As far as known the females do not grow larger than 4 to 4.50 meters.  The 4 fetus were between 22.4 cm. and 23.7 cm. long. The food of intermedius consists mainly of fish: in the stomach specimens a great amount of small stones were found ranging from 440 gr. to 920 gr.  The egg laying period takes place mainly in January and the juveniles hatch in March. The eggs are white; their average size is about 8 em. long and 5 cm. wide. Up to 70 eggs were found in a nest.  March 3, 1957 a nest 43 cm. deep and 51 cm. wide at the base, was found in the Río Guaviare. It was situated on a, sand-bank, about 40 meters from the river. The first eggs were found in a depth of 27 cm.  The temperature in the nest, measured before the eggs were taken out, was slightly higher than outside. The shell of the eggs was quite elastic while still in the nest, but became hard soon after being taken out.  Of the 57 eggs found in the nest, 54 contained fetus, the remaining 3 were rotten.  The fetus already moved; but still had a well developed vitelline sack. The female, a specimen a about 3 meters long, remained in the water, splashing furiously. Cr. intermedius undergoes an aestivation the dry season in the Llanos Orientales (Rivers Arauca, Meta, Vichada) but no information is available from the Guaviare area. The Orinoco Crocodile of the Guaviare area digs no subterranean caves as does Cr. acutus from the Magdalena region and other rivers of northern Colombia.  Due to excessive hide-hunting Cr. intermedius was practically exterminated in large areas and became rather scarce even in remote regions.